2004
DOI: 10.1007/s00120-003-0506-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychoonkologie

Abstract: Cancer and psychiatric symptoms commonly co-occur. The frequency is about 50%, and those most important for urology are depression, anxiety, and probably post-traumatic stress disorder. There is a strong relationship between psychological distress and cancer pain. This review provides information on diagnostic and therapeutic strategies for psychiatric diseases, which are important for oncology patients in urology. Special advice is given for the doctor-patient relationship and communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Kollner et al [12] note that there is a 50% comorbidity rate of psychiatric conditions, including depression, anxiety, and posttraumatic stress disorder in urology cancer patients. Pinto and Trunzo [13] reported that mood and body esteem in breast cancer survivors was higher in women who exercised.…”
Section: Cancermentioning
confidence: 98%
“…Kollner et al [12] note that there is a 50% comorbidity rate of psychiatric conditions, including depression, anxiety, and posttraumatic stress disorder in urology cancer patients. Pinto and Trunzo [13] reported that mood and body esteem in breast cancer survivors was higher in women who exercised.…”
Section: Cancermentioning
confidence: 98%